2013
DOI: 10.1089/acm.2012.0466
|View full text |Cite
|
Sign up to set email alerts
|

Massage Therapy for Patients with Metastatic Cancer: A Pilot Randomized Controlled Trial

Abstract: The study results showed that it is feasible to provide therapeutic massage at home for patients with advanced cancer, and to randomize patients to a no-touch intervention. Providing therapeutic massage improves the quality of life at the end of life for patients and may be associated with further beneficial effects, such as improvement in pain and sleep quality. Larger randomized controlled trials are needed to substantiate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 15 publications
1
59
0
2
Order By: Relevance
“…8,9,[11][12][13][14][17][18][19] In addition, in the 3 low-quality studies with PEDro scores <6, we also observed a significant effect of massage in reducing cancer pain (SMD −1.28 [95% CI −1.71 to −0.86]; P < .00001; see Supplemental Figure 4B). …”
Section: Effects Of Massage Therapy According To the Methodological Qmentioning
confidence: 54%
See 4 more Smart Citations
“…8,9,[11][12][13][14][17][18][19] In addition, in the 3 low-quality studies with PEDro scores <6, we also observed a significant effect of massage in reducing cancer pain (SMD −1.28 [95% CI −1.71 to −0.86]; P < .00001; see Supplemental Figure 4B). …”
Section: Effects Of Massage Therapy According To the Methodological Qmentioning
confidence: 54%
“…Body massage was significantly effective in 7 studies (SMD −1.11 [95% CI −1.50 to −0.71]; P < .00001; Supplemental Figure 3A). 8,9,[13][14][15]17,19 In particular, foot reflexology was significantly effective in 4 studies (SMD −1.46 [95% CI −2.45 to −0.47]; P = .004; Supplemental Figure 3B). 10,11,16,18 Aroma massage had significant effects in 2 studies (SMD −1.26 [95% CI −1.83 to -0.69]; P < .0001; Supplemental Figure 3C).…”
Section: Effects Of Massage Therapy According To Massage Typementioning
confidence: 99%
See 3 more Smart Citations